Proceedings of the 36th International MATADOR Conference - Hinduja, Srichand; Li, Lin (Springer London : Imprint: Springer, 2010)
Presented here are 130 refereed papers given at the 36th MATADOR Conference held at The University of Manchester in July 2010. The MATADOR series of conferences covers the topics of Manufacturing Automation and Systems Technology, Applications, Design, Organisation and Management, and Research. The proceedings of this conference contain original papers contributed by researchers from many countries on different continents. The papers cover the principles, techniques and applications in aerospace, automotive, biomedical, energy, consumable goods and process industries. The papers in this volume reflect: • the importance of manufacturing to international wealth creation; • the emerging fields of micro- and nano-manufacture; • the increasing trend towards the fabrication of parts using lasers; • the growing demand for precision engineering and part inspection techniques; and • the changing trends in manufacturing within a global environment.